Beauty is not Only Skin Deep: Food Ethics and Consequences to the Value Chain - Silva, Vivian Lara; Kasemodel, Marcia Gabriela C.; Makishi, Fausto; Pião, Roberta de Castro Souza; Santos, Vinícius Machado dos (Internext, 2019)
The contemporary context in which the food industry is set up instigates a new product conception towards food ethics. However, how effectively does this perspective materialize on the gondolas of retail chains? In order to bring some elements to discussion, this article presents an exploratory study based on the decoding of information contained in food labels marketed in Brazil. In total, 287 labels regarding four categories (juices, snacks, chocolates, and yogurt) were analyzed using the Reverse Engineering methodology. The results indicate a movement of brand differentiation structured in actions conducted inside (a result of product and process engineering) and outside (regarding relationship engineering along the value chain). In other words, the internalization of innovations in products and processes (inside perspective) and; the development of vertical cooperation and coordination relations outside the company (outside perspective). In this sense, participation in globally connected markets is described as a driver of differentiation strategies regarding ethical aspects in the food processing industry and has direct effects on the vertical structures of firms, as suggested by the value chain literature.